PENGARUH METODE PEMBELAJARAN BERBASIS MASALAH TERHADAP SELF-EFFICACY DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DITINJAU DARI KEMAMPUAN AWAL MATEMATIKA SISWA SMA - Muhammad Faruq Masri; Suyono Suyono; Pinta Deniyanti (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2018)
ABSTRACTThis study aims to investigate the ability of self-efficacy and improvement of students' mathematical problem-solving ability through learning by using Problem Based Learning (PBL) methods. This study uses quasi experimental methods with final test control design for mathematical self-efficacy and pre-test post-test for mathematical problem-solving ability in terms of students' early math skills. The sample of this research is the students of class X IPA in SMA 3 and SMA 4 Kabupaten Tanggerang in odd semester of academic year 2017/2018 as many as 96 students. The result of this researh are (1) There is an improvement of mathematical problem-solving ability of students who are treated with PBL methods is better than students who get conventional learning; (2) There is an interaction between learning method and early math ability (KAM) to improving students mathematical problem-solving ability; (3) There is an improvement of mathematical problem-solving ability in students with high KAM; (4) There is no improvement of mathematical problem-solving ability in students with low KAM; (5) Self-efficacy of students who are treated with PBL methods is better than students who get conventional learning; (6) There is an interaction between learning method and early math ability (KAM) to self-efficacy of students; (7) There is different self-efficacy in students with high KAM; (8) There is no different of self-efficacy in students with low KAM.Keywords: Problem Based Learning, Problem-Solving Ability, Self-Efficacy